2019
DOI: 10.21273/jashs04775-19
|View full text |Cite
|
Sign up to set email alerts
|

Drought Stress–induced Physiological and Metabolic Changes in Leaves of Two Oil Tea Cultivars

Abstract: Oil tea (Camellia oleifera) is an important edible oil tree. However, its growth and yield are strongly limited by drought. This study investigated the physiological and metabolic responses of two common oil tea cultivars, Huajin and Changlin53, to moderate and severe drought stress. Based on the photosynthetic and physiological indices, ‘Changlin53’ may be more tolerant to drought than ‘Huajin’. A total of 41 key metabolites induced by drought stress, including 12 amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…The decrease in irrigation water levels led to increase the proline content of pomegranate seedlings (Hamdy et al, 2016). Qu et al, (2019) found that under moderate drought stress, the contents of amino acids (such proline content) were significantly enhanced; however, under severe drought stress, the synthesis ability of amino acids was increased.…”
Section: Leaves Chemical Constituentsmentioning
confidence: 99%
“…The decrease in irrigation water levels led to increase the proline content of pomegranate seedlings (Hamdy et al, 2016). Qu et al, (2019) found that under moderate drought stress, the contents of amino acids (such proline content) were significantly enhanced; however, under severe drought stress, the synthesis ability of amino acids was increased.…”
Section: Leaves Chemical Constituentsmentioning
confidence: 99%
“…The leaf measurement area was 6 cm 2 and the air flow rate was 500 µmol•s -1 . The instantaneous water-use efficiency (WUE) was calculated as WUE = P n /T r (Qu et al, 2019). CO 2 was supplied at a concentration of 400 µmol•mol -1 using small cylinders.…”
Section: Photosynthetic Physiological Parametersmentioning
confidence: 99%
“…In China, cultivated C. oleifera is one of the four major woody oil species, followed by the tung tree (Vernicia fordii Hemsley), walnut (Juglansregia), and Chinese tallow tree (Sapium sebiferum) [1,2]. The tea oil extracted from C. oleifera seeds is an edible oil known as "eastern olive oil," because of its high nutritional value and health benefits [3]. Tea oil has a similar chemical composition to that of olive oil; both contain high amounts of unsaturated fatty acids [4].…”
Section: Introductionmentioning
confidence: 99%